If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x-4 + 0.5x + 0.2(2x-4+8)=26
We simplify the equation to the form, which is simple to understand
2x-4 + 0.5x + 0.2(2x-4+8)=26
Simplifying terms in parentheses
2x-4 + 0.5x + 0.2*(+4+2x)=26
Reorder the terms in parentheses
2x-4 + 0.5x+( + 0.8 + 0.4x)=26
Remove unnecessary parentheses
+2x-4 + 0.5x + 0.8 + 0.4x=+26
We move all terms containing x to the left and all other terms to the right.
+2x + 0.5x + 0.4x=+26+4-0.8
We simplify left and right side of the equation.
+2.9x=+29.2
We divide both sides of the equation by 2.9 to get x.
x=10.0689655172
| (2x+7)6=-7x+4 | | 2u-8+3v= | | 8(x+7.4)-8x+12= | | 37x+8=6(6x+1) | | -6+g=11 | | 37+w=5w-35 | | 5x-8x+3=x-6+9 | | 5x-3(2x-1)=8x-1 | | .04(x+10)+.6x=29 | | 3x+7-5(x+1)=5x+8 | | 10(6)+10-6(-7-6)= | | x^5=7 | | 400x+3858=6374 | | n+n+2=206 | | n+n+1+n+2=111 | | n+n+1=5 | | -5x-5=40 | | x^2+8=8x-8 | | 2r^2+10r+12=0 | | 3(2x-1.3)=2(3x-2.1)-3(x-0.7) | | .5(x+50)+.3x=41 | | (7n+4)= | | -2x=-3y+10 | | 4(8+2x)=5x+11 | | (7n+4)(n+5)= | | 9x-3x-2=0 | | 450.00-35.00= | | (3x-1)(4x-3)= | | x+7=x-2 | | 3x=6y-9 | | 5q=-25 | | 3x-(2x+5)=0 |